ANALYSIS OF SIMPLE SENTENCE STRUCTURE IN ENGLISH: FUNCTIONAL SYNTAX APPROACH - Ida cahyani (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2021)
Many approaches in syntax give a deeper chance to analyze the sentence beyond its formal structure even though those approaches focus on the issues of words category, function and role in a sentence construction. The approach of functional syntax emphasizes the sentence structure on the ‘role’ of each function in each category of words that construct the sentence. This paper analyzes simple sentence in English especially declarative sentence to describe the constituent units and the function structure of simple sentence with active voice. The analysis employs Morley’s Functional Syntax Approach to identify the function of each english active sentence element and describe the structure of a simple sentence in English. The results of analysis show that simple sentence can have a syntactic function structure ofS-P-O, S-P-C, or S-P-ACIRC with a functional role structure which is principally composed of semantic roles of the filler elements of each function in the form of participant-process-entity/thing; participant-process-quality or participant-process-feature/quality. The semantic role of the verbs in a sentence determine the elements of filler before and after the verb given in a sentence. Keywords: Functional syntax, verbs, semantic role, syntactic function.